Anti-GBM Disease in Pregnancy: Acute Renal Failure Resolved After Plasma Exchange, Hemodialysis, and Steroids. (31st December 2015) - Adnan, Mohammed Muqeet; Morton, Jordan; Hashmi, Syed; Abdul Mujeeb, Sufyan; Kern, William; Cowley, Benjamin D.
Antiglomerular basement membrane (GBM) disease presenting during pregnancy is uncommon. We present a case of a pregnant female who presented with acute renal failure requiring dialysis due to anti-GBM disease. She responded well to plasma exchange, high-dose steroids, and hemodialysis. Cyclophosphamide was discussed but not given at the patient's request due to concerns for the well-being of the fetus. Unfortunately, she suffered a spontaneous abortion in her eighth week of pregnancy. Subsequently, she had progressive improvement in her renal function and became hemodialysis independent at 2 weeks after diagnosis. Her renal function returned to baseline 3 months after diagnosis. We present this case in detail and review the literature regarding anti-GBM disease in pregnancy.